PENGELOLAAN WAKAF PONDOK PESANTREN AL-HIKMAH SIRAMPOG KABUPATEN BREBES - Setiawan, Edi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
The purpose of this study is to reveal the waqf management practices in Al-Hikmah Islamic Boarding School and contribution to education and community empowerment, and uncover the factors supporting and managing endowments in the foundation. This research used qualitative research methods with case study management approach. The results of this study showed that Endowments foundation is managed in synergy with the management of education. Management practices applied this foundation is still traditional. Utilization endowments for community empowerment is realized through activities which can be grouped into four areas: Economics, Department of Structure, and Education and Religious Affairs.